Synthesis of Chiral Assembly from Achiral Octadehydrotribenzo[14]annulene Derivative by Using a Twofold Helical Hydrogen-Bonding Template - Hisaki, Ichiro; Kometani, Eriko; Shigemitsu, Hajime; Tohnai, Norimitsu; Miyata, Mikiji (Synlett, 2015)
Chiral supramolecular architecture was synthesized from the achiral noncentrosymmetric title compound by using a twofold helical hydrogen-bonding network as a template.
Keywords: annulenes; macrocycles; carboxylic acid; chirality; supramolecular chemistry